ISLAM AND COLONIALISM: THE RESPONSE OF THE MUSLIMS IN THE SOUTHERN PHILIPPINES TO WESTERN COLONIALISM AND LEGACIES - Lantong, Abdul M (PEOPLE: International Journal of Social Sciences, 2018)
Since the onset of Western colonialism in the Philippines, the Muslims in the South indefatigably resisted Western colonialism to preserve their cherished values, identity, culture, and freedom. Using various social change theories, writers and researchers tried but failed, to explain the motivation of Muslims behind this phenomenon. Although Islam played a vital role in shaping the attitude of the Muslims, none of the concerned scholars yet attempted to understand the issue from the Islamic perspective. Thus, the present study aims to investigate the relation between Islam and the responses of Muslims in the Southern Philippines to the challenges which the western colonialism posed upon them. The researcher used historical analysis of data gathered through library research. The paper showed that Islam played a paramount role in shaping the Muslims’ attitudes and responses to the challenge of Western colonialism. Islamic principle served as the pillar of their struggle for decolonization. Hence, without Islam, the western colonial powers would have successfully colonized the Muslims in the Southern Philippines similar to what they did to the people of Luzon and Visayas Islands.